E-pocket book media PBL-based for problem solving ability and student learning motivation - Istiana, Rita; Munandar, Rifki Risma; Choerunnisa, Nur Asri (Universitas Wiralodra, 2024)
This study is based on students’ inability to solve problems in psychotropic material, which is caused by students' low reasoning power and tendency to memorize the material. To address these issues, consider using PBL-based e-pocket book media used for this study. The purpose of this study is to develop e-pocket book media based on PBL that are feasible, practical, and effective in improving students' problem-solving skills and motivating them to learn. The research was conducted in November 2022 - May 2023. The RnD research method was used in conjunction with the ADDIE development design. Interview guidelines, learning observations, expert assessment sheets, teacher and student response questionnaires, and student motivation questionnaires in learning were used to assess learning. The qualitative data analysis was obtained from media and material expert advice, teacher and student response questionnaires, student motivation questionnaires, learning observations, and interviews. The validation result of media experts yielded a quantitative 96% very feasible category while material expert validation yielded a 92% very feasible category. The results of the teacher's response questionnaire were 91%, while the student response was 89% in the very practical category. A questionnaire on student motivation in learning after using e-pocket book media was also obtained by 86%. Furthermore, the results of the independent sample t-test, show the result where Tcount>Ttable. It can be concluded that PBL-based e-pocket book media is very feasible and practical to use in learning and can improve students' problem-solving abilities on psychotropic material and motivate students in learning.